Efektivitas Aplikasi Desmos Terintegrasi PjBL pada Pembelajaran Matematika Multimedia Ditinjau dari Kemampuan Literasi Matematis - Bulan Nuri; Lissa Zikriana; Iqbal Iqbal (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effectiveness of the desmos application integrated with PjBL in terms of mathematical literacy skills, the effectiveness of multimedia mathematics learning in terms of mathematical literacy skills and the effectiveness of the desmos application integrated with PjBL in multimedia mathematics learning in terms of mathematical literacy skills. This research design is quasi-experiment with a post-test only control group design. The research subject were 60 students of senior high schools at SMA Negeri 3 Bireuen with a total research population of 102 students. The sample in this study was determined by a convenience sampling technique. The instrument used was a diagnostic test consisting of three questions based on mathematical literacy skills. The data were analyzed using the classical completeness test, different proportion test and t-test. Based on the research findings, it is deducible that the Desmos application yields better results when integrated with PjBL concerning mathematical literacy skills. Moreover, mathematics learning supported with multimedia is more efficacious for enhancing mathematical literacy skills. Lastly, when evaluating mathematical literacy skills, combining Desmos application with PjBL and multimedia in mathematics learning proves to be the most effective approach